Production of benzenecarboxylic acids from two typical Chinese subbituminous coals by oxidation in aqueous sodium hypochlorite solution and insights into structural characteristics. (1st July 2019) - Liu, Fang-Jing; Zong, Zhi-Min; Zhu, Ying; Wei, Xian-Yong; Zhu, Xiang-Nan; Tang, Ming-Chen; Huang, Zai-Xing
Graphical abstract: Highlights: High yields of BCAs were produced from ZSBC and SFSBC via oxidation by NaOCl. Different BCAs were generated from different aromatic precursors via the oxidation. ZSBC has much more polyaryl moieties with Car -Car bridged bonds than SFSBC. SFSBC contains much more highly condensed aromatics than ZSBC. The O2 − dissociated from NaOCl could play an important role in producing BCAs. Abstract: Zhundong subbituminous coal (ZSBC) and Shenmu-Fugu subbituminous coal (SFSBC) were oxidized in aqueous sodium hypochlorite solution at 30 °C for 10 h to produce valuable benzenecarboxylic acids (BCAs) and to understand structural characteristics of the 2 typical Chinese subbituminous coals. Fourier transform infrared spectrometer, gas chromatograph/mass spectrometer, and direct analysis in real time ionization source coupled to an ion trap mass spectrometer were used to characterize the resulting products from the oxidation. The results show that the distributions of functional groups, molecular masses, and group components of the products from ZSBC and SFSBC oxidation are largely similar. Non-chlorine BCAs are the dominant carboxylic acids (CAs) from the oxidation and the total yields of BCAs from ZSBC and SFSBC oxidation are 15.6 wt% and 16.5 wt% based on organic matter in ZSBC and SFSBC, respectively, suggesting that both coals contain abundant polycyclic or condensed aromatic rings (ARs). Various BCAs, including cata -condensed aromatics, polyaryls, and peri -condensed aromatics, were generated from different aromatic precursors (APs) via the oxidation. According to the distributions of BCAs, ZSBC is rich in polyaryl moieties with Car -Car bridged linkages between the ARs, while SFSBC contains much more highly condensed ARs. O2 − dissociated from NaOCl could play a crucial role in producing BCAs from the ARs in ZSBC and SFSBC. In addition, some nitrogen-containing CAs were produced and their possible APs in ZSBC and SFSBC were speculated.